PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF SOLMATH PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL DI KELAS ONLINE - Teguh Bayu Saputra; Aan Nurfahrudianto; Samijo Samijo (UNEJ e-Proceeding, 2022)
This research is based on observation. Based on the observation, it was known that the students tend to feel bored in learning Mathematics. The research aim is to produce interactive learning media products using Microsoft Powerpoint based on android application on the material of a two-variable linear equation system. Moreover, the subjects of this study consisted of media experts, material experts, practitioners, and limited trials of 6 10th grade students. The researchers used research and development methods (R & D) to produce a product so that it was feasible to use. The data were obtained from the validation results of material experts, media experts, practicing experts, and limited trials. From the results of the validation carried out by researchers, each expert obtained results for material experts got a percentage of 88 percent categorized as very valid, and media experts got a percentage of 94 percent categorized as very valid. Furthermore, expert practitioners received a percentage of 95.5 percent which was categorized as very valid, and the results of a limited trial got a percentage of 82 percent which was categorized as valid. In addition, it can be concluded that the SolMath interactive learning media on the material of a two-variable linear equation system is feasible to use. Keywords: SolMath, interactive media, math learning